2013 SID Honors and Awards. Issue 2 (1st March 2013) - Donelan, Jenny
Abstract : This year's winners of the Society for Information Display's Honors and Awards include Dr. Isamu Akasaki, who will receive the Karl Ferdinand Braun Prize for his seminal contributions to the development of high‐quality single‐crystal GaN‐based semiconductors and their PN‐junction blue LEDs and lasers; Dr. Marc Baldo, who will receive the Jan Rajchman Prize for his outstanding contributions to the discovery of phosphorescent‐OLED devices; Dr. Hoi‐Sing Kwok, who will be awarded the Slottow‐Owaki Prize for providing education and training in display technology to many students and professionals in the Asia region through the creation of a display research center; and Dr. Shigeo Mikoshiba, who will receive the Lewis & Beatrice Winner Award for his sustained exceptional contributions to SID for over 30 years.